BULAN SURA DALAM PERSPEKTIF ISLAM - Partin Nurdiani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2013)
This article reveals the Sura the rituals of Javanese society in Suramonth. They believe that it is Tundan dhemit, a time when there was agroup of ghosts who are looking for prey, especially those who are unawareand careless. The people serve this ceremony to protect themselvesfrom this disaster. Meanwhile In Islam Sura or Muharram is the specialmonth because there were many histories about prophets and their struggle.This phenomenon results a controverse which arouse to sin.